Would You Use It With a Seal of Approval? Important Attributes of 2,4-Dinitrophenol (2,4-DNP) as a Hypothetical Pharmaceutical Product - Bleasdale, Emma E.; Thrower, Sam N.; Petróczi, Andrea (Frontiers in Psychiatry, 2018)
Background: 2,4-dinitrophenol (2,4-DNP) is an effective but highly dangerous fat burner, not licensed for human consumption. Death cases reported for 2,4-DNP overdose, particularly among young adults, have raised concerns about the ineffective regulatory control, lack of education and risks associated with impurity and the unknown concentration of 2,4-DNP purchased on the Internet. Methods: Using a sequential mixed method design and based on a hypothetical scenario as if 2,4-DNP was a licensed pharmaceutical drug, first we conducted a qualitative study to explore what product attributes people consider when buying a weight-loss aid. Focus group interviews with six females and three males (mean age = 21.6±1.8 years) were audiorecorded, transcribed verbatim and subjected to thematic analysis. Sixteen attributes were identified for the Best-Worst Scale (BWS) in the quantitative survey with 106 participants (64% female, mean age = 27.1±11.9 years), focusing on 2,4-DNP. Demographics, weight satisfaction and risk for eating disorder data were collected. Results: In contrast to experienced users such as bodybuilders, our study participants approached 2,4-DNP cautiously. Attributes of 2,4-DNP as a hypothetical weight-loss drug comprised a range of desirable and avoidable features. Of the 16 selected attributes, BWS suggested that long-term side effects were the most and branding was the least important attribute. Effectiveness and short-term side effects were also essential. Those in the >25 years group showed least concerns for legality. Neutral BWS scores for cost, treatment, degree of lifestyle changes required and specificity required for the hypothetical weight-loss drug to be effective were likely caused by disagreement about their importance among the participants, not indifference. Conclusions: With advances in research, 2,4-DNP as a pharmaceutical drug in the future for treating neurogenerative diseases and potentially for weight loss is not inconceivable. Caution is warranted for interpreting the BWS scores. Owing to the difference in what data represent at individual vs. population levels, with pooled data the method correctly identifies attributes by which most people are satisfied but misrepresents attributes that are individually very important but not universally agreed. Whilst this may be an advantage in marketing applications, it limits the utility of BWS as a research tool.